2021
DOI: 10.3390/ijerph18052257
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Relationships, Regional Differences, and Driving Mechanisms between Economic Development and Carbon Emissions from the Farming Industry: Empirical Evidence from Rural China

Abstract: The coordinated development of the economy, resources, and environment is a key aspect of sustainable development. China’s rapid agricultural modernization has been accompanied by the continuous growth of rural economic aggregate and carbon emissions from the planting industry. However, the quantitative relationship between these two factors and its internal mechanism are not yet fully understood. In this paper, the Intergovernmental Panel on Climate Change (IPCC) method is used to calculate the carbon emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In order to further grasp the relationship between environmental pollution and industrial structure change and economic growth mode since China's reform and opening up, this paper selects 34 years' time series data from 1980 to 2013 as research data, and The Compilation of 65 years' Statistical Data of New China is the main source of data in this paper. Specifically, variable selection and data explanation mainly include the following five aspects [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to further grasp the relationship between environmental pollution and industrial structure change and economic growth mode since China's reform and opening up, this paper selects 34 years' time series data from 1980 to 2013 as research data, and The Compilation of 65 years' Statistical Data of New China is the main source of data in this paper. Specifically, variable selection and data explanation mainly include the following five aspects [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…While economic agglomeration might improve technical efficiency, it also produces additional resource consumption and demand, resulting in a rebound effect in which resource savings from improved technical efficiency were countered by increasing carbon emissions from economic expansion. 23 Furthermore, the extension of urbanization as a result of economic agglomeration will influence agricultural infrastructure in surrounding rural regions, increase agricultural costs and the degree of fragmentation of cultivated land, and adversely affect agricultural productivity. 24 The effect of economic agglomeration on environmental pollution depends on the combined effect of the above positive and negative effects, and therefore some empirical studies have found the relationship between the two to be uncertain or non-linear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results show that regions with solid carbon sink capacity are more likely to become carbon refuges in the future. Due to the high cost of CCUS technology and the significant reduction of new energy power generation costs, the industry develops slowly and has high uncertainty (Liu et al 2021a , b , c ). Therefore, this paper selects the carbon sink capacity (forest carbon sink) as the influencing factor of the corresponding carbon neutralization emission reduction targets and does not consider CCUS and other technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To achieve China’s regional carbon emission reduction goals, many scholars explore China’s carbon emissions from different perspectives. Liu et al ( 2021a , b , c ) found out the main driving factors of carbon emissions of various regional transportation industries by analyzing the carbon intensity differences of China’s regional transportation industries. Gao et al ( 2021 ) used the input–output method to explore the impact of China’s provincial large-scale population migration on trade, empirically analyzing the effect of population transfer and trade carbon transfer on regional carbon emissions and targeted suggestions for China’s provincial carbon emission reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation